Personality and Entrepreneurship - Alexander Kritikos (Global Labor Organization (GLO), 2022)
Does personality matter? Is an individual who is open to experience more or less likely to become an entrepreneur? Is it better to score low or high in agreeableness for surviving as an entrepreneur? To the extent that personality captures one part of entrepreneurial abilities, which are usually unobservable, the analysis of traits and personality characteristics helps better understanding such abilities. This article reviews research on the relationship between personality and entrepreneurship since 2000 and shows that possessing certain personality characteristics will make it more likely that an individual will start an own business and hire staff. More specifically, with respect to the entry decision, research finds that nearly all so-called Big Five factors as well as several specific personality characteristics influence the entry probability into entrepreneurship. Further, entrepreneurs are more likely to hire, the higher they score in risk tolerance, trust, openness to experience, and conscientiousness. However, different factors such as low scores in agreeableness, the only Big Factor that does not affect entrepreneurial entry, influence entrepreneurial survival. And for some of characteristics that influence entrepreneurial entry, like high scores in the factor openness for experience or in risk tolerance, "revolving door effects" are found, explaining why some entrepreneurs subsequently exit again the market.
Keywords: L26; 330; entrepreneurship; personality